O desenvolvimento sócio cognitivo na Educação Infantil: a importância da atividade lúdica na perspectiva de Wallon - Souza, Luana Soares de (Universidade Federal do Tocantins, 2021)
The present work refers to the final result of a bibliographical research entitled "Sociocognitive development in early childhood education: the importance of playful activity in Wallon's perspective". The same is part of a bibliographic study that emerged during the process of the licenciatura course in pedagogy. Having as general objective to understand from a bibliographical study how the play activity in the perspective of Wallon contributes to the educational development of Early Childhood Education. To that end, we had the following problematic: How does play activity from Wallon's perspective contribute to the educational development of Early Childhood Education? In this way, seeking to answer the problematic presented here, we pondered the following specific objectives: To analyze the perspective of Wallon and his contributions in the educational development of the children of the children's education; to discuss the relevance of play to the educational development of children in early childhood education; and describe about caring, playing and educating in pedagogical practice in early childhood education. The work is structured in four chapters, which are organized in subtopics. In order to reach the objective of this work and thus to answer the problematic we had as theoretical contribution the following authors Alfandéry (2010); Friendmann (2012); Kishimoto (1997-1998-2003-2009); Wallon (2007); Vygostky (1991); Piaget (1971); Official Documents (1988-1996-1998); among other authors and documents that discuss the subject under discussion. Thus, the results showed that playing in the educational environment is not a mere pastime, and that educators need to be less directive, less controlled and more open to listen to what children talk, want, complain about and play invent.